2019
DOI: 10.1002/adhm.201901030
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of Magnesium in Bone Biomineralization

Abstract: infections, and biochemical disorders could be addressed with a wide variety of bone substitutes or implants. [1] Bone is a mineralized composite of inorganic and organic units, mostly hydroxyapatite (HA) and type I collagen, respectively. [2] To mimic the nature of bone, scientists have researched several aspects of the biomaterials of bone substitutes or implants over the past decades, [3] and chemical composition of them is a primary consideration. Currently, magnesium (Mg 2+ ) and Mg 2+ alloys are gaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 42 publications
3
73
0
2
Order By: Relevance
“…Our analysis also showed differences in the intracellular Mg concentration depending on the treatment. Mg concentration is typically increased in the early stage of mineralization and gradually decreases and reaches a stable concentration in the late mineralization phase [49]. Therefore, decreased Mg concentration and increased Ca/P ratio for cells treated with DEVs suggested that DEVs stimulated the nucleation and mineralization process.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also showed differences in the intracellular Mg concentration depending on the treatment. Mg concentration is typically increased in the early stage of mineralization and gradually decreases and reaches a stable concentration in the late mineralization phase [49]. Therefore, decreased Mg concentration and increased Ca/P ratio for cells treated with DEVs suggested that DEVs stimulated the nucleation and mineralization process.…”
Section: Discussionmentioning
confidence: 99%
“…Before harvesting the embryos, pregnant female mice were sacrificed by an overdose of anesthetic. [ 8a,31 ] More details are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that magnesium is an essential element for HA cations in bone tissue and abnormal concentrations of magnesium ions cause alterations in the structure of HA. 69,70 More and more studies have shown that the effect of magnesium on bone metabolism was mainly reected in the activation of osteoblasts and inhibition of osteoclasts to promote osteogenic development and maintain the strength and density of bones at a certain concentration. 71,72 It has been proposed that 6-10 mM magnesium ions can improve osteogenic activity and differentiation, however, when the concentration of magnesium ions exceeded 18 mM, it had the opposite effects.…”
Section: Magnesium Ionsmentioning
confidence: 99%